Utilizing Integrated Teaching Approach In Teaching Literature To ESL Learners: A Systematic Review - Mercado, Jomar (International Journal of Language and Literary Studies, 2025)
The success rate of language learning hinges on the effectiveness of teaching approaches employed by teachers in ESL classes, particularly in literature teaching. Thus, this study explored the use of the Integrated Approach in literary teaching to ESL learners. Furthermore, this study ventured into teaching approaches utilized by the teachers that made up the Integrated Approach, the effectiveness of the approach to literary teaching, and the potential interactive activities that can be implemented using the approach. Systematic literature review method was used in the study and findings revealed that teachers used various literature teaching approaches, having the information-based approach as the most commonly employed while the stylistic approach was the least. Furthermore, the Integrated Approach was seen as effective in literary comprehension and appreciation, critical and creative thinking enhancement, and more so in language learning. Lastly, extensive question exercises, lecture sessions, discussion, utilization of differentiated teaching strategies, audio-visual materials, and collaborative activities were seen to be the best activities and practices in literary teaching. In conclusion, the findings of the study may help both teachers and learners in literary education. This may help in the design of an instructional module for teachers relative to the use of the Integrated Approach in teaching literature.